Otx2 Requires Lmx1b to Control the Development of Mesodiencephalic Dopaminergic Neurons. - Orna Sherf; Limor Nashelsky Zolotov; Keren Liser; Hadas Tilleman; Vukasin M Jovanovic; Ksenija Zega; Marin M Jukic; Claude Brodski (PLoS ONE, 2015)
Studying the development of mesodiencephalic dopaminergic (mdDA) neurons provides an important basis for better understanding dopamine-associated brain functions and disorders and is critical for establishing cell replacement therapy for Parkinson's disease. The transcription factors Otx2 and Lmx1b play a key role in the development of mdDA neurons. However, little is known about the genes downstream of Otx2 and Lmx1b in the pathways controlling the formation of mdDA neurons in vivo. Here we report on our investigation of Lmx1b as downstream target of Otx2 in the formation of mdDA neurons. Mouse mutants expressing Otx2 under the control of the En1 promoter (En1+/Otx2) showed increased Otx2 expression in the mid-hindbrain region, resulting in upregulation of Lmx1b and expansion of mdDA neurons there. In contrast, Lmx1b-/- mice showed decreased expression of Otx2 and impairments in several aspects of mdDA neuronal formation. To study the functional interaction between Otx2 and Lmx1b, we generated compound mutants in which Otx2 expression was restored in mice lacking Lmx1b (En1+/Otx2;Lmx1b-/-). In these animals Otx2 was not sufficient to rescue any of the aberrations in the formation of mdDA neurons caused by the loss of Lmx1b, but rescued the loss of ocular motor neurons. Gene expression studies in Lmx1b-/- embryos indicated that in these mutants Wnt1, En1 and Fgf8 expression are induced but subsequently lost in the mdDA precursor domain and the mid-hindbrain organizer in a specific, spatio-temporal manner. In summary, we demonstrate that Otx2 critically depends on Lmx1b for the formation of mdDA neurons, but not for the generation of ocular motor neurons. Moreover, our data suggest that Lmx1b precisely maintains the expression pattern of Wnt1, Fgf8 and En1, which are essential for mid-hindbrain organizer function and the formation of mdDA neurons.